2014
DOI: 10.1039/c4ta04467c
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of selenium cathodes via in situ formation of protective solid electrolyte layer

Abstract: The lithium/selenium (Li/Se) rechargeable battery chemistry offers a higher energy density than traditional Li ion battery cells. However, high solubility of polyselenides in suitable electrolytes causes Se loss during electrochemical cycling, and leads to poor cycle stability. This study presents a simple technique to form a protective, solid electrolyte layer on the cathode surface. This protective layer remains permeable to Li ions, but prevents transport of polyselenides, thus dramatically enhancing cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…In carbonate electrolytes, the interface generated on Se‐based cathodes has been proven to be very efficient in facilitating electrode kinetics and forbidding side reactions. [ 31,41,51,52,218 ] However, no such interface can be observed in the case of ether‐based electrolytes, which is ascribed to the high chemical stability of the ether solvent. [ 52 ] Optimizing or even constructing reliable interface between the electrode and electrolyte would be a potential pathway to achieve advanced LSeBs.…”
Section: Blocking Layer Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In carbonate electrolytes, the interface generated on Se‐based cathodes has been proven to be very efficient in facilitating electrode kinetics and forbidding side reactions. [ 31,41,51,52,218 ] However, no such interface can be observed in the case of ether‐based electrolytes, which is ascribed to the high chemical stability of the ether solvent. [ 52 ] Optimizing or even constructing reliable interface between the electrode and electrolyte would be a potential pathway to achieve advanced LSeBs.…”
Section: Blocking Layer Engineeringmentioning
confidence: 99%
“…For example, Lee et al. [ 218 ] found that a protective layer was formed on the cathode in the electrolyte with FEC after an activation cycle ( Figure a), and consequently delivered a much more stable cycling performance as compared to the samples without FEC and/or activation cycle (Figure 17b). Further postmortem examination suggests that the Li anode of cycled LSeBs with FEC was quite smooth, whereas a thick insulating layer comprising deposited lithium polyselenides was noted in the cycled cells without FEC (Figure 17c,d).…”
Section: Blocking Layer Engineeringmentioning
confidence: 99%
“…The first problem can be partially avoided by adopting porous carbon, which contains the sulfur inside nanopores based on overlapping of adsorption potentials914151617. The second problem could be largely circumvented by employing the appropriate electrolyte additive(s) to form the desirable SEI18. However, these strategies are still not satisfactory, and further improvements are required.…”
mentioning
confidence: 99%
“…17,45,[95][96][97][98] Typically, FEC is used to enhance the cycling efficiency of Si anodes through growth of polymeric fluorine containing SEI and multiple studies focused on its chemical composition and mechanisms of inducing effective cross-linking. [99][100][101] Similar mechanisms may be expected to take place in case of conversion cathodes if their first discharge cycle potential range was similarly low.…”
mentioning
confidence: 99%